A Systematic Review and Meta-Analysis of the Effectiveness of Neuroprotectants for Paclitaxel-Induced Peripheral Neuropathy - Leen, Alisha Joan; Yap, Dominic Wei Ting; Teo, Chong Boon; Tan, Benjamin Kye Jyn; Molassiotis, Alex; Ishiguro, Hiroshi; Fan, Sarah Wei Xian; Sundar, Raghav; Soon, Yu Yang; Bandla, Aishwarya (Frontiers in Oncology, 2022)
BACKGROUND: Paclitaxel-induced peripheral neuropathy (PIPN) is a disabling side effect of paclitaxel with few effective preventive strategies. We aim to determine the efficacy of pharmacological and non-pharmacological neuroprotective interventions in preventing PIPN incidence. METHODS: Biomedical literature databases were searched from years 2000 to 2021 for trials comparing neuroprotective interventions and control. Meta-analysis was performed using the random effects model. The primary outcome was the incidence of PIPN. RESULTS: Of 24 relevant controlled trials, 14 were eligible for meta-analysis. Pooled results from seven non-pharmacological trials were associated with a statistically significant 48% relative reduction of PIPN risk with low heterogeneity. Conversely, pooled results from six pharmacological trials were associated with a significant 20% relative reduction of PIPN risk with moderate heterogeneity. Both pharmacological and non-pharmacological approaches appear effective in reducing PIPN incidence in the treatment arm compared to control (pooled RR<1). CONCLUSION: Current evidence suggests both interventions may reduce PIPN risk. Non-pharmacological interventions appear more effective than pharmacological interventions.